한국의 안보와 사드(THAAD) - 박건영; Kun Young Park (한국과 국제정치, 2016)
한국과 미국의 사드 배치 결정은 한반도에서의 전면전을 가정한다. 그러나 필자는 이러한 가정이 갖는 현실성은 낮으며, 우발적 요인에 의한 전면전이 발발한 경우에도 사드의 군사적 효율성은 높지 않다고 판단한다. 오히려 한국은 북한의 위협이나 도발이 전면전으로 비화하지 않도록 하는 관리체계를 구축·확충하고, 전면전 비화 시를 상정하여 보다 효율적 방어체계를 갖추는 데 역량을 집중해야 한다고 제시한다. 나아가, 필자는 국제정치적·경제적‘비용 대편익’분석에 기초하여, 사드 배치가 오히려 한국의 안보를 감소시킬 수 있다고 지적한다. 필자는, 한국의 외교장관이 언급했듯이, “고난도 외교 사안의 고차방정식에 대해 1·2차원적으로 단순하게”접근해서는 안 된다고 주장하며, 다차원의 요인들을 시의적으로 결합한‘전략적-실용주의’의‘역동적 패키지’를 대안으로 제시한다. Korea and the U.S. have decided to deploy a THAAD system in Korea under the assumption that North Korea could start a full-scale war against Korea by launching its nuclear ballistic missiles. But the author determines that the assumption is not realistic. Moreover, he suggests that, even though a dispute can be escalated to a full-scale war, the THAAD is not a viable means to neutralize North Korea’s missile attack. The author maintains that, based on his cost-benefit analysis, the THAAD in Korea may even decrease Korea’s security. He provides an alternative that derives from what he calls the strategic-pragmatic approach.